PENDAMPINGAN PELATIHAN STRATEGI PEMASARAN DAN PRODUKSI USAHA PABRIK TAHU PUTRA PAGADUNGAN MANDIRI JAYA - Adriansah, M.Pd Adriansah; Evi Purwaningsih; Sri Utami (Muttaqien Publishing Pusat Penelitian dan Pengabdian kepada Masyarakat STAI DR. KH.EZ. Muttaqien Purwakarta, 2023)
Tofu is a traditional Indonesian food made from soybeans which is rich in protein and makes a healthy food. In its activities, there are problems faced by this tofu business, namely the distance from the tofu production site to the market and the high price of soybeans, which are problems faced by Mr. Dindin as the owner of the tofu factory, Putra Pagadungan Mandiri Jaya, Kertamanah Village, Sukasari District, Purwakarta Regency. The purpose of this service is to provide tofu production training for housewives and marketing strategy training as well as solutions to tofu owners for existing problems. In this trial using qualitative methods, field observations, interviews, and documentation studies. To overcome the problem of marketing tofu, there are five strategies offered to the owner of the tofu factory. To overcome the problem of rising soybean prices as the main ingredient for making tofu, there are several alternative solutions including reducing the size of tofu and reducing the use of soybeans by replacing soybeans with non-soybeans.